Role of Long-Acting Porcine Sequence ACTH (Acton Prolongatum) Stimulated Cortisol in Assessing Glucocorticoid Status in COVID-19 Patients - Vijay S. R. Danda; Chandrashekhar Bhandiwad; Sharmila Palle; Srinivas R. Paidipally; Vivek Kyatham (Indian Journal of Endocrinology and Metabolism)
Introduction: Conflicting research on cortisol levels and COVID-19 mortality prompted this study to comprehensively assess glucocorticoid status, its links to severity and outcomes, and the role of Acton prolongatum-stimulated cortisol. Methods: This is a prospective observational study, conducted in 100 RT-PCR-positive COVID-19 patients of mild, moderate, and severe grades from June 2021 to May 2023. Random cortisol, plasma ACTH, and action prolongatum stimulated cortisol were measured, categorized, and analyzed. Results: Among 100 patients, 25 had severe disease, 35 had moderate disease, and 40 had mild disease. In the same study group, 88 recovered and 12 expired from the COVID-19-related cause. The median random basal serum cortisol level (median (IQR): 10.2 (8) vs. 11.6 (9.7) vs. 16.2 (9.5) mcg/dl; P value 0.06), median delta value (median (IQR): 6.3 (5.8) vs. 7.6 (4.8) vs. 10.9 (5.6) mcg/dl; P value < 0.001), and median plasma ACTH (median (IQR): 13 (14.7) vs. 14.4 (14.1) vs. 22.3 (13) pg/ml; P value = 0.002) were lower in severe group subjects than in the moderate and mild group. When patients were labeled as adrenal insufficiency based on random basal serum cortisol < 10 mcg/dl or delta value < 9 mcg/dl, 48% of patients had adrenal insufficiency. There was a linear correlation between random basal and ACTH-stimulated cortisol (r = 0.908, P value < 0.001). Conclusion: The study highlights the significance of adrenal function in COVID-19 prognosis and suggests for routine random cortisol and ACTH assessments for glucocorticoid evaluation.